(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article examines effective phonetic training techniques that contribute to improving pronunciation among English as a Second Language (ESL) students. It emphasizes that pronunciation is a core component of communicative competence, and that systematic phonetic instruction significantly enhances learners’ ability to produce clear, accurate, and intelligible speech. The study explores various pedagogical techniques such as articulatory training, minimal pair drills, auditory discrimination, phonetic transcription, and the use of technological tools. It also highlights the importance of combining explicit phonetic explanation with communicative practice. The paper concludes that effective phonetic training helps learners overcome native language interference, boosts their confidence, and promotes fluency and naturalness in spoken English.